ACHIEVEMENT MOTIVATION TRAINING (AMT) SEBAGAI UPAYA PREVENTIF PERILAKU PROKRASTINASI AKADEMIK MAHASISWA - Alawiyah, Ela Minchah Laila; Subekti, Tabah; Anggraeni, Viana Tety (Edukasi: Jurnal Penelitian dan Artikel Pendidikan, 2016)
This study aims to provide the Achievement Motivation Training (AMT) as a Preventive of Student ProcrastinationBehavior at Muhammadiyah University of Magelang. The method in this study is experiment (One Group Pretest-PosttestDesign). Students are measured by using procrastination scale. The data analysis used to test the hypothesis of this study bynon-parametric statistical analysis of two interconnected samples test using wilcoxon signed ranks to see the difference betweenacademic procrastination behavior before and after training.Based on the analysis of pretest and posttest data, it is knownthat there is a difference between pretest and posttest with sig value 0.924 (Sig> 0,05), it means the hypothesis is rejected thatthere is no significant difference of academic procrastination between before training (pretest) and after training (posttest), so thetraining that has been conducted in this research is less able to give effect to the decrease of the student?s academic procrastinationbehavior based on the procrastination scale, but when viewed from the interview and observation result during the training andposttest shows that the students are very enthusiastic and inspired by the activity, To abstain from academic procrastinationbehavior. It is also seen that one month after the training, students are more excited to come to the class on time, more visiblytough, cheerful, and more eager not to delay doing tasks.